Reduced Healthcare Resource Utilization in Patients With Chronic Insomnia 24 Months After Treatment With Digital CBT-I: A Matched-Control Study. (April 2023) - Forma, Felicia; Knight, Tyler; Baik, Rebecca; Wallace, Matthew; Malone, Dan; Xiong, Xiaorui; Velez, Fulton; Thorndike, Frances; Maricich, Yuri
Abstract: Introduction: This analysis examined the impact of a digital therapeutic for treating chronic insomnia (currently marketed as Somryst ®, at the time called Sleep Healthy Using The internet [SHUTi]) on healthcare resource use (HCRU) by comparing patients treated with the digital cognitive behavioral therapy for insomnia (dCBTi) to patients not treated with dCBTi, but with insomnia medications. Methods: A retrospective observational study using health claims data was conducted in two cohorts across the United States: patients who registered for dCBTi (cases) between June 1, 2016 and October 31, 2018 (index date) vs. patients who did not register for dCBTi but initiated a second prescription for an insomnia medication in the same time period (controls). Observation period was 16–24 months. No other inclusion/exclusion criteria were used. Control patients were matched using a nearest neighbor within-caliper matching without replacement approach. Incidence rates for HCRU encounter type were calculated using a negative binomial model for both cohorts. Costs were estimated by multiplying HCRU by published average costs for each medical resource. Results: Evaluated were 248 cases (median age 56.5 years, 57.3% female, 52.4% treated with sleep-related medications) and 248 matched controls (median age 55.0 years, 56.0% female, 100.0% treated with sleep-related medications). Over the course of 24 months post-initiation, cases had significantly lower incidences of inpatient stays (55% lower, IRR: 0.45; 95% CI: 0.28–0.73; P= 0.001), significantly fewer emergency department (ED) visits without inpatient admission (59% lower; IRR: 0.41; 95% CI: 0.27–0.63; P <0.001), and significantly fewer hospital outpatient visits (36% lower; IRR: 0.64; 95% CI: 0.49–0.82; P<0.001). There was also a trend for fewer ambulatory surgical center visits (23% lower; IRR: 0.77; 95% CI: 0.52–1.14; P= 0.197) and fewer office visits (7% lower; IRR: 0.93; 95% CI: 0.81–1.07; P=0.302) with the use of SHUTi. Use of sleep medications was more than four times greater in controls vs. cases, with 9.6 (95% CI: 7.88–11.76) and 2.4 (95% CI: 1.91–2.95) prescriptions/patient, respectively ( P <0.001). All-cause per-patient HCRU costs were $8, 202 lower over 24 months for cases vs. controls, driven primarily by a lower incidence of hospitalizations (-$4, 996 per patient) and hospital outpatient visits (-$2, 003 per patient). Conclusions: Patients with chronic insomnia who used a digital CBTi treatment had significant and durable real-world reductions in hospital inpatient stays, ED visits, hospital outpatient visits, and office visits compared to matched controls treated with medications. Funding: Pear Therapeutics (US), Inc.